Pengaruh Capital Adequacy Ratio Terhadap Return On Asset pada PT. Bank Muamalat, Tbk Periode 2010-2019 - Siti Nurcahayati (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the effect of the Capital Adequacy Ratio on the Return on Assets at PT. Bank Muamalat, Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Capital Adequacy Ratio obtained an average value of 51.66%. The return on assets variable obtained an average value of 3.32%. Capital Adequacy Ratio has a positive and significant effect on Return on Assets with a regression equation value of Y = 2.329 + 0.019X, and a correlation coefficient value of 0.674 or has a strong level of relationship with a determination value of 45.5%. Hypothesis testing obtained a significance of 0.000 <0.05.